Prevalence of adiposity‐based chronic disease in middle‐aged adults from Czech Republic: The Kardiovize study - Juan P. Gonzalez‐Rivas; Jeffrey I. Mechanick; José Pantaleón Hernandez; María M Infante‐Garcia; Iuliia Pavlovska; José R. Medina‐Inojosa; Sarka Kunzova; Ramfis Nieto‐Martinez; Jan Brož; Luca Busetto; Geraldo A Maranhao Neto; Francisco Lopez‐Jimenez; et al. (Wiley, 2021)
Abstract Aims/Hypothesis The need for understanding obesity as a chronic disease, its stigmatization, and the lack of actionability related to it demands a new approach. The adiposity‐based chronic disease (ABCD) model is based on adiposity amount, distribution, and function, with a three stage complication‐centric rather than a body mass index (BMI)‐centric approach. The prevalence rates and associated risk factors are presented. Methods In total, 2159 participants were randomly selected from Czechia. ABCD was established as BMI ≥ 25 kg/m2 or high body fat percent, or abdominal obesity and then categorized by their adiposity‐based complications: Stage 0: none; Stage 1: mild/moderate; Stage 2: severe. Results ABCD prevalence was 62.8%. Stage 0 was 2.3%; Stage 1 was 31.4%; Stage 2 was 29.1%. Comparing with other classifiers, participants in Stage 2 were more likely to have diabetes, hypertension, and metabolic syndrome than those with overweight, obesity, abdominal obesity, and increased fat mass. ABCD showed the highest sensitivity and specificity to detect participants with peripheral artery disease, increased intima media, and vascular disease. Conclusion/Interpretation The ABCD model provides a more sensitive approach that facilitates the early detection and stratification of participants at risk compared to traditional classifiers.